Laudato Si’: Can it inspire a sufficiency revolution in architecture? - David Ness (Techne, 2025)
Arguably, the 2015 papal encyclical letter Laudato Si’, on care for our common home, is particularly relevant nowadays as a way to combat rampant overconsumption and its impact on climate change and inequity – including within the building sector. Thus far, measures adopted by the sector to contain emissions have proved ineffective. Any gains via energy efficiency, ‘clean tech’ and renewables have been outpaced by growth in built floor area, which is projected to double by 2050. In addition to being a major theme of the encyclical, the concept of ‘sobriety’ (sufficiency) was introduced by the IPCC in 2022 as a way to achieve the necessary rapid and deep cuts in emissions. Involving practices and measures that avoid demand for resources while enabling well-being for all, the concept has only recently come to the fore. A milestone report on Sufficiency and the Built Environment was launched at COP29, with a potentially major impact upon architecture and building. While exploring these implications, the article examines the proposition that Laudato Si’ may inspire a sufficiency revolution embracing more innovative and holistic ways of tackling global challenges.